2020
DOI: 10.35333/eriss.2020.172
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Boş Zaman Yönetiminin Değerlendirilmesi

Abstract: Boş zaman günlük hayatımızı ve gelecek yaşantımızı belirleyen umutların ve hayallerin yer aldığı iç dünyamızda özgürlüğü hissettiğimiz zamanlardır. Bu zamanın yönetiminde ise kişisel beceri yanında sosyal ortamdan kaynaklı birçok etkinin varlığı söz konusudur. Bu çalışmanın amacı, "Boş Zaman Yönetimi Ölçeğinin" uygulamasını yapmaktır. Araştırmaya Marmara Üniversitesi Spor Bilimleri Fakültesinde öğrenim gören 170 üniversite öğrencisi katılmıştır. Ölçek 15 madde ve 4 alt boyuttan oluşmaktadır. Bu alt boyutlarda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Durhan, Akgül and Karaküçük (2017) determined that individuals engaged in recreational swimming had higher levels of time management skills. Demir and Alpullu (2020) found that students studying in sports sciences faculties (teaching, coaching, and sports management) obtained high scores in all dimensions of time management. Considering that effective time planning and management are crucial for achieving success in sports careers, it is possible to argue that individuals engaged in sports may possess competence in time management.…”
Section: Discussionmentioning
confidence: 96%
“…Durhan, Akgül and Karaküçük (2017) determined that individuals engaged in recreational swimming had higher levels of time management skills. Demir and Alpullu (2020) found that students studying in sports sciences faculties (teaching, coaching, and sports management) obtained high scores in all dimensions of time management. Considering that effective time planning and management are crucial for achieving success in sports careers, it is possible to argue that individuals engaged in sports may possess competence in time management.…”
Section: Discussionmentioning
confidence: 96%
“…By engaging in more physical activities and effectively managing time as one ages, individuals can potentially enhance their quality of life, particularly in terms of physical well-being. Demir & Alpullu [ 59 ] conducted a study which revealed that age and the extent of activity participation significantly influenced the management of free time. Consistent findings were noted in other investigations [ 74 ].…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…According to Mokhtari et al [ 75 ], a sedentary lifestyle has a negative impact on the ability to use time in an international study conducted on students. Other studies on student samples found that physical activity positively influenced free time management [ 59 , 63 , 76 ]. Furthermore, it is reported in foreign sources examining the effect of physical activity on quality of life that participating in physical activity increases one’s level of well-being [ 77 ].…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the literature on leisure was examined, it can be said that some demographic characteristics affect leisure time management and the benefit to be gained from this time (Çakır, 2017;Demir and Alpullu, 2020). It is assumed that the variables of gender, marital status, educational status, experience in the institution and weekly leisure in this study will create significant differences in the answers given by the participants to the questions in the scales.…”
Section: Discussionmentioning
confidence: 99%